Factores externos e impactos sobre la productividad total factores de empresas de manufacturas: Evidencia del caso peruano; External factors and impacts on total factor productivity of companies: Evidence of the Peruvian case - Mario Delfín Tello Pacheco (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– In contrast to the literature on the total factor productivity of companies, focused on internal factors, this work examines the impact of three external factors on the growth rate of total factor productivity (TFP) of manufacturing companies in Peru, period 2002-2019. Using the Annual Economic Survey of manufacturing firms in Peru, the results of the panel data estimate with instrumental variables reveal that in countries that export primary products and derivatives thereof, the terms of trade provide incentives for companies to increase productivity. On the contrary, domestic GDP growth shocks, in countries dependent on domestic demand and production, discourage TFP growth given that domestic production and TFP are more associated with increases in capital, particularly those of imported origin. Finally, trade liberalization processes through reductions in preferential tariffs on both products and inputs help, although to a lesser extent and statistical significance, to increase the growth rate of companies' TFP, particularly in exporting companies.
Keywords: D24; F13; 330; External factors; tariffs reduction; total factor productivity